1975
DOI: 10.1136/thx.30.5.554
|View full text |Cite
|
Sign up to set email alerts
|

Forced expiratory time--its reliability as a lung function test.

Abstract: . (1975). Thorax, 30, The time taken for a forced expiration can be measured easily with stopwatch and stethoscope. Over the last 30 years many observers have been attracted by this simplicity and have proposed a number of uses for forced expiratory time (FET) as a lung function test. Recently, McFadden and Linden (1972) and Cochrane et al. (1974a) have drawn attention to FET as a possible measurement of obstruction to airways of less than 2 mm internal diameter. Both groups suggest a good correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
3

Year Published

1977
1977
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 12 publications
1
24
3
Order By: Relevance
“…We also found a significant correlation between FET a and FEV 1 /FVC, and FEV 1 and FEV 1 % in BA patients. Along with studies [12,13] , we revealed a significant correlation between FET a and FET s but only in asthma patients. A substantially weaker correlation in healthy subjects was found.…”
Section: Macdonald Et Al (1975)supporting
confidence: 71%
See 2 more Smart Citations
“…We also found a significant correlation between FET a and FEV 1 /FVC, and FEV 1 and FEV 1 % in BA patients. Along with studies [12,13] , we revealed a significant correlation between FET a and FET s but only in asthma patients. A substantially weaker correlation in healthy subjects was found.…”
Section: Macdonald Et Al (1975)supporting
confidence: 71%
“…In the study of [4] the mean FET s in healthy non-smokers was 9.8 (9.2-10.4) s with shorter exhalation time commonly seen in young adults. [13] reported that both FET as and FET s have a high intrasubject variability (CV of FET as was 25%; CV of FET s was 21.4%). At the same time Kern and Patel (1991) [9] believed that performing the FE maneuver can be standardized, thereby decreasing the intrasubject variability of FET as .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower limit of lung volumes was considered to be -20% of the predicted value. The lower limit for FEV,% was considered to be equal to the predicted FEV,%-5% (25).…”
Section: Airway Morphologymentioning
confidence: 99%
“…The dipyridamole stress protocol of our institution used a higher dipyridamole dose (0.7 mg/kg body weight) than is currently recommended and low-level (25 W) bicycle stress to enhance image quality [5]; both factors have to be considered, yet seem unlikely to have seriously affected our results. Reproducibility is crucial for pulmonary function testing [6], and is indicated by invariable expiratory efforts and global volume parameters. However, regional pulmonary function parameters reflecting obstruction in smaller airways [7] indicated peripheral bronchospasm.…”
Section: Discussionmentioning
confidence: 99%